Prolyl hydroxylase inhibition protects against murine MC903-induced skin inflammation by downregulating TSLP - Gupta, Anupriya; Song, Mi Hye; Youn, Dong Hyuk; Ku, Dohyeon; Sasidharan Nair, Varun; Oh, Kwonik (Frontiers in Immunology, 2024)
Previously, we reported an anti-inflammatory effect of mTORC1 in a mouse model of type 2 skin inflammation. TSLP, one of the epithelial cell-derived cytokines, was upregulated by Raptor deficiency or rapamycin treatment, which was inhibited by dimethyloxalylglycine (DMOG). However, it remains unclear how DMOG regulates TSLP expression and type 2 skin inflammation. In this study, we investigated the protective effect of DMOG on MC903 (calcipotriol)-induced type 2 skin inflammation. Morphological and immunological changes were assessed by H-E staining, flow cytometry and RT-qPCR. DMOG treatment attenuated MC903-induced skin inflammation in a T cell-independent manner. The anti-inflammatory effect of DMOG was accompanied by downregulation of TSLP and IL-33, and supplementation with recombinant TSLP and IL-33 abolished the effect of DMOG. MC903 increased ROS levels in skin tissue, which was prevented by DMOG. Furthermore, the ROS scavenger N-acetylcysteine (NAC) downregulated TSLP and ameliorated MC903-induced skin inflammation, as did DMOG. Finally, the effect of DMOG on ROS and TSLP was reduced by HIF knockdown. These results suggest that DMOG downregulates TSLP and ROS through the HIF pathway, which reduces MC903-induced skin inflammation.